Popular movements and state formation in revolutionary Mexico : the agraristas and cristeros of Michoacán - Purnell, Jennie, 1957- (Duke University Press, 1999)
Purnell reconsiders peasant partisanship in the cristiada of 1926-29, one episode in the broader Mexican Revolution.